MINTAQADA KLASTERLARNI RIVOJLANTIRISHDA ZAMONAVIY MODELLARNI QOʻLLASH MASALALARI (Marketing Jurnali, 2025)
This article highlights the issues of applying modern models in the development of clusters in the region. In addition, scientific proposals and practical recommendations have been developed for the application of modern models in regional cluster developm ent.
Keywords: mintaqa; klaster; model; davlat; innovatsion klaster; aglomeratsiya; hududiy rivojlanish